2005
DOI: 10.21273/horttech.15.4.0777
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Firmness of Pickling Cucumber Cultivars

Abstract: Fruit firmness is one of the most important quality aspects in the production of pickling cucumbers (Cucumis sativus) for industry. This study compared the fruit firmness of different cultivars and evaluated the usability of different firmness variables. Firmness of fruit of five to six cultivars from a cultivar experiment was measured penetrometrically over 3 years. The maximum load needed to penetrate the skin, distance at maximum load, load at the end of the measurement, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Several studies have been conducted on the changes in nutrient components in pickled vegetables (Peng & Geisman, 1976;Javier et al, 2004;Montano et al, 2004). Meanwhile, several authors have studied the changes of the textural properties of pickled vegetables (Suojala-Ahlfors, 2005;Yoo et al, 2006;Cho & Buescher, 2012) and found that the texture of the salted vegetables softened during the pickling process. A large number of studies have suggested that the texture degradation of processed fruits and vegetables was mainly ascribed to the solubilisation and nonenzymatic depolymerisation of the cell wall pectin (Sila et al, 2006;De Roeck et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the changes in nutrient components in pickled vegetables (Peng & Geisman, 1976;Javier et al, 2004;Montano et al, 2004). Meanwhile, several authors have studied the changes of the textural properties of pickled vegetables (Suojala-Ahlfors, 2005;Yoo et al, 2006;Cho & Buescher, 2012) and found that the texture of the salted vegetables softened during the pickling process. A large number of studies have suggested that the texture degradation of processed fruits and vegetables was mainly ascribed to the solubilisation and nonenzymatic depolymerisation of the cell wall pectin (Sila et al, 2006;De Roeck et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of cucumber (Cucumis sativus L.) fruits is evaluated primarily on the basis of freshness (Sakata et al 2008). Texture is known to be a major factor affecting cucumber quality (Breene et al 1972;Thompson et al 1982;Horie et al 2004;Suojala-Ahlfors 2005;Yoshioka et al 2009Yoshioka et al , 2010. Mechanical properties on relatively homogeneous parenchyma have been investigated to describe texture of plant materials, and fracture tests with various breaking methods (tensile, compression, bending, wedging and cutting) have been commonly conducted (Vincent 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties on relatively homogeneous parenchyma have been investigated to describe texture of plant materials, and fracture tests with various breaking methods (tensile, compression, bending, wedging and cutting) have been commonly conducted (Vincent 1994). The puncture test of mesocarp (flesh) and/or endocarp (placenta in the seed cavity) has been adopted by many researchers to evaluate the texture of cucumbers (Breene et al 1974;Bourne 1982;Thompson et al 1982Thompson et al , 1992McFeeters and Lovdal 1987;Horie et al 2004;Sakurai et al 2005;Suojala-Ahlfors 2005;Sakata et al 2008). Another method to measure the texture of cucumbers was performed using a wedge-shaped probe to mimic human mastication (Dan et al 2003a;Kohyama et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The almost symptom-free fruits of CGMMV-infected cucumber plants did not reveal such significant deviations from the control, neither in fruit tissue structure nor in texture values. Differences in texture values between individual cultivars such as 'Liszt' and 'Platina' exist naturally, as studies have shown so far [36,37]. Pasteurization and long storage could amplify these differences and are thus clearly measurable even in the fresh or pasteurized state.…”
Section: Discussionmentioning
confidence: 99%